PERANCANGAN APLIKASI SATUDIKTI UNTUK MENGINTEGRASIKAN MODUL-MODUL DIKTI MENGGUNAKAN FLUTTER - Naufal Rachmandani (2023)
The use of mobile devices is now quite widespread in various circles, by using an application on a mobile device an application is easier to use because it can be accessed anywhere and anytime. Currently the Directorate General of Higher Education has several directorates, each of which has its own application, with the current number of applications many users do not know that the Directorate General of Higher Education has any applications and the uses of each of these applications, meanwhile the applications currently being made are aimed at users around universities and information is also spread across several dikti applications, some applications also have their own news and announcements, so it will be difficult if users have to switch between applications to find information. In this study, the author and the dikti team will design an application that can become a single door in accessing dikti modules and has been integrated into one system using Single Sign On (SSO). The author uses the Scrum methodology and uses the dart programming language with the Flutter framework. The results of this study are a Satudikti application based on Android and iOS mobile which is expected to be useful and to make it easier for the community to access dikti modules.